Prevalence of Geriatric Syndromes and Satisfaction of Service in Older People Receiving Annual Health Screening at the Check-up Clinic, Siriraj Hospital - Harisd Phannarus; Supakorn Chansaengpetch; Tirathat Virojskulchai; Napaporn Pengsorn; Pensri Chaopanitwet; Usa Vannachavee; Jirawit Wong-ekkabut; Ananya Treewisoot; Sunun Thanasamut; Angkana Jongsawadipatana; Weerasak Muangpaisan (Siriraj Medical Journal)
Objective: To assess the prevalence of geriatric syndromes (GSs) and evaluate service satisfaction among older patients attending a comprehensive geriatric check-up clinic (CGCC) at Siriraj Hospital.